Bibliometric Analysis of Biochar's Use in Surface Water Treatment - Laili, Fitria; Rizqy, Fachria; Wisnu, Prayogo; I Wayan Koko, Suryawan; Gerry, Andhikaputra; Dion, Awfa; Rifka, Noor Azizah (INTI International University, 2023)
The utilization of biochar holds promise as a viable method for the preservation of water resources and the remediation of wastewater. The objective of this study is to evaluate the advancements achieved in the field of biochar research pertaining to the remediation of surface water. The review was conducted by systematically collecting data from Scopus and doing bibliometric analysis. This study utilized the Scopus database to retrieve data pertaining to countries, institutions, highly cited articles, keywords, emerging subjects, and prospective research directions. Furthermore, the VOSviewer bibliometric software was utilized to assess the scholarly citations in this research paper. The results indicate that significant advancements have been achieved in this area of study during the year 2015. A total of 48 works has been indexed by Scopus, a renowned academic database, across 28 distinct international journals. A significant proportion of researchers primarily operate within the United States, often engaging in collaborative efforts with their counterparts from China. This article attempts to study the bibliography on the biochar for surface water treatment, identify popular topics, and discern the fields of future studies in this discussion. Furthermore, it investigates future research in the field of biochar will primarily concentrate on optimizing the synthesis of biochar and exploring its potential use in the treatment of heavy metals and organic chemicals.